Modelling the influence of submesoscale processes on phytoplankton dynamics in the northern South China Sea - Xiu, Peng; Guo, Lin; Ma, Wentao (Frontiers in Marine Science, 2022)
Submesoscale processes in the ocean vary rapidly in both space and time, and are often difficult to capture by field observations. Their dynamical connection with marine biology remains largely unknown because of the intrinsic link between temporal and spatial variations. In May 2015, satellite chlorophyll data demonstrated high concentration patches in the edge region between mesoscale eddies, which were higher than those in the cyclonic eddy core region in the northern South China Sea (NSCS). The underlying mechanisms were examined with a high-resolution physical-biological model. By tracking Lagrangian particles in the model, this study shows that the edge region between eddies is a submesoscale frontal region that is prone to intense upwelling and downwelling motions. We identified two key submesoscale mechanisms that affect nutrient transport flux significantly, submesoscale fontal dynamics and submesoscale coherent eddies. The dynamics associated with these two mechanisms were shown to be able to inject subsurface nutrients into the upper layer, generate the high chlorophyll patch, and alter phytoplankton community structure in the NSCS. This study shows the importance of submesoscale processes on phytoplankton dynamics in the NSCS and highlights the need for high-resolution observations.